Penggunaan Media Audiovisual dalam Pengajaran Musik - Wiflihani Wiflihani (Gondang: Jurnal Seni dan Budaya, 2021)
This article aims to explain the use of audiovisual media in learning music. To carry out teaching through audiovisual media, it is necessary to prepare a learning unit, choose the correct audiovisual media and adjust it to a musical instrument or teaching topic, to know the duration of the audiovisual media, which must be adjusted to the lesson hours. To prepare students, they are given a general explanation of the contents of the learning video, then they play back and prepare the equipment for a smooth learning experience. Follow-up: After watching a film or video, the teacher also did examples of playing music, thinking, and asking questions to students to find out how well the students understood the material.